Cross-border mergers in Europe. Volume 2 (Cambridge, 2011)
"This discussion of the Cross-Border Merger Directive and its implementing legislation in each Member State of the European Union and the European Economic Area provides companies and their advisors with useful insight into the legal framework applicable to, and the tax treatment of, cross-border mergers throughout the European Economic Area. Analysis of the Community rules laid down in the Cross-Border Merger Directive and the Community rules on the tax treatment of cross-border mergers is complemented by chapters on the implementing legislation in each Member State, prepared in accordance with a common format and contributed by a practitioner from each state. Annexes contain the Cross-Border Merger Directive (Annex I), the Parent-Subsidiary Directive (Annex II) and a list of the implementing legislation in each Member State (Annex III)."